Pengaruh model pembelajaran discovery terbimbing terhadap aktivitas dan hasil belajar IPA di MIN 1 Langsa - Fera, Fera Ariani; Sari, Rita; Rahayu, Nina (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2022)
The purpose of this study was to determine the effect of the guided discovery learning model on students' science learning activities and outcomes at MIN 1 Langsa in the 2020/2021 academic year. The type of this research is experimental research. The population in this study were first-grade students of MIN Langsa consisting of 5 classes with 28 students per class. The sampling technique used in this study was simple random sampling. The sample used in this study was adjusted to the number of students in the covid-19 period where the number of students had to be divided by two and students entered according to the specified schedule. Based on the results of this study, it can be explained that the experimental class using the guided discovery learning model increased more than the control class. this shows that the Ha hypothesis can be accepted and Ho is rejected or the use of the guided discovery learning model is efficient to improve student learning outcomes in science subjects. The results showed that the learning outcomes of the experimental class using the Guided Discovery learning model were higher than the control class using the Group Investigation learning model, namely 78.39% of the experimental class and 71.61% in the control class